2020
DOI: 10.5937/scriptamed51-27863
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of physical activity with stress, depression and anxiety in female students

Abstract: Background/Aim: The period of beginning of studies is a stressful period of life in which students are expected to develop skills and abilities with which they will be able to take on the most important roles in all areas of social activity. Physical activity (PA) triggers and remodels mental health. The aim of the study was to determine the correlation between PA and stress, anxiety and depression in female students. Methods: Epidemiological observational study was performed and included a representative samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
1
0
1
Order By: Relevance
“…No association was found between physical activity with depression, anxiety and stress which is supported by the previous studies (28,32,34,35). Conversely, few studies found significant association between physical activity and depression subscale (32,33,34).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…No association was found between physical activity with depression, anxiety and stress which is supported by the previous studies (28,32,34,35). Conversely, few studies found significant association between physical activity and depression subscale (32,33,34).…”
Section: Discussionsupporting
confidence: 53%
“…No association was found between physical activity with depression, anxiety and stress which is supported by the previous studies (28,32,34,35). Conversely, few studies found significant association between physical activity and depression subscale (32,33,34). A cohort study conducted in the United State during pandemic showed that the physical activity among respondents declined from the 2019 to 2020 spring cohort and significantly associated with depression (31).…”
Section: Discussionmentioning
confidence: 70%
“…Específicamente, el nivel de actividad física está asociado positivamente con el bienestar, 2023;12 (1):114-136 y negativamente con la ansiedad y síntomas de depresión en la población adolescente (10). Además, se ha encontrado una relación negativa tanto en ansiedad como en depresión, con los niveles de actividad física en estudiantes universitarias (11). A su vez, en otro estudio, se estableció una relación entre las capacidades físicas y la memoria en población infantil de 12 años (8).…”
Section: Introductionunclassified